Solitary Intestinal Lymphoid Tissue Provides a Productive Port of Entry for Salmonella enterica Serovar Typhimurium - Halle, Stephan (American Society for Microbiology, 2007)
Oral infection of mice with Salmonella enterica serovar Typhimurium results in the colonization of Peyer's patches, triggering a vigorous inflammatory response and immunopathology at these sites. Here we demonstrate that in parallel to Peyer's patches a strong inflammatory response occurs in the intestine, resulting in the appearance of numerous inflammatory foci in the intestinal mucosa. These foci surround small lymphoid cell clusters termed solitary intestinal lymphoid tissue (SILT). Salmonella can be observed inside SILT at early stages of infection, and the number of infected structures matches the number of inflammatory foci arising at later time points. Infection leads to enlargement and morphological destruction of SILT but does not trigger de novo formation of lymphoid tissue. In conclusion, SILT, a lymphoid compartment mostly neglected in earlier studies, represents a major site for Salmonella invasion and ensuing mucosal pathology.